Symptomatic COVID-19 Positive Parturients Posted for Lower Segment Caesarean Section - M Jisha; M Mohan David (Journal of Clinical and Diagnostic Research, 2022)
Since the outbreak of the Coronavirus Disease-2019 (COVID-19) pandemic many elective cases were postponed worldwide. But emergency Lower Segment Caesarean Sections (LSCS) is one surgery which can’t be postponed at any cause, since two lives are at risk. The present case series reports 16 symptomatic COVID-19 patients in whom emergency LSCS was performed. The aim of presenting the series was to analyse how far the clinical and laboratory findings were deranged in such patients and to find out whether the current anaesthetic techniques were safe in these patients. Out of a total of 157 COVID-19 positive patients who had undergone LSCS in the study, 16 presented with symptoms such as fever, cough, dyspnoea, rhinitis, headache and palpitation. Six (37.5%) were preterm. Seven patients had elevated C-Reactive Protein (CRP) (>5 mg/L). Liver function tests abnormalities were seen in 5 (31.25%). Most of the patients had elevated D-dimer of which (>1500 ng/mL) were seen in seven. The most common indication was foetal distress. COVID pneumonia was an indication for LSCS in 3 (18.75%). All the surgeries were performed under subarachnoid block. Of the four patients who had fall in oxygen saturation two were admitted in Intensive Care Unit (ICU) and one required Non Invasive Ventilation (NIV). There were no mortalities. Thus, LSCS can be done safely under subarachnoid block even in symptomatic COVID-19 parturients. Elevation of D-dimer is common in pregnancy and it does not always indicate severe COVID-19 disease.